2005
DOI: 10.1021/ma0502708
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Core−Shell Type Molecularly Imprinted Particles:  Molecular Imprinting into Aromatic Polyimide Coated on Silica Spheres

Abstract: Core-shell type imprinted spherical particles were prepared by using a conventional polymer solution coating method. A poly(amic acid) was synthesized by step-reaction polymerization of the diamines (1:19 mole ratio of the diamine monomer-template complex:4,4′-oxydianiline) and the pyromellitic dianhydride in N,N-dimethylacetamide at ambient temperature. The diamine monomer-template complex was synthesized by the reaction of the diamine having an isocyanato group and estrone (template) having a phenol moiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Lvov and co‐workers have also reported the self‐assembly of tannic acid with strong and weak polycations and produced capsules with the lowest permeability at pH 5–7 78. Many other polymers have also been used to create the shell layer, such as PMAA by Caruso et al,51 Wortman et al,53 and Sukhishvili et al,77 polyvinylamine by Shi et al,79 polyimide by Chang and co‐workers,80 and polyalanine (PANI) and polypyrrole by Yang et al6 and Oh and co‐workers 14…”
Section: Methodsmentioning
confidence: 99%
“…Lvov and co‐workers have also reported the self‐assembly of tannic acid with strong and weak polycations and produced capsules with the lowest permeability at pH 5–7 78. Many other polymers have also been used to create the shell layer, such as PMAA by Caruso et al,51 Wortman et al,53 and Sukhishvili et al,77 polyvinylamine by Shi et al,79 polyimide by Chang and co‐workers,80 and polyalanine (PANI) and polypyrrole by Yang et al6 and Oh and co‐workers 14…”
Section: Methodsmentioning
confidence: 99%
“…PI/inorganic composite materials have combined the special structure of inorganic component and excellent properties of PI and have become a type of promising materials focused on various applications [27][28][29]. In the past years, a number of researches have been carried out on the preparation and characterization of homogeneous polyimide-silica composite materials [30][31][32][33][34][35][36][37][38][39]. Most of them focused on the preparation of homogeneous PI/SiO 2 hybrid films via the sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission electron microscopy (TEM) image showed that SiO 2 was surfacecoated in PI and the PI/SiO 2 nanocomposite particles were core-shell structure. Kim [39] successfully fabricated coreshell-type molecularly imprinted spherical particles by using a conventional polymer solution coating method. A poly(amic acid) was used for the coating of a silica sphere and converted to the polyimide layer, which had a rigid structure suitable for molecular imprinting.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid these troubles, core shell structural MIPs have been introduced recently . A thin layer of MIPs was polymerized on top of some solid chains, such as monodispersed polystyrene seeds, silica and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%